A control design procedure for plants with random initial conditions and constraints on the mean square actuator rates - FRANGOS, C.; YAVTN, Y. (International journal of systems science, 1995)
This paper proposes a controller synthesis methodology to satisfy practical performance specifications for plants with random initial conditions and subject to constraints on the mean square actuator rates. A discrete linear optimal controller structure is employed. A standard mathematical programming algorithm is used to compute the state weighting matrix Q such that the performance specifications are satisfied subject to constraints on the mean square actuator rates. The design procedure is demonstrated via an example dealing with the design of a flight control system.